2003
DOI: 10.1124/jpet.102.047118
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Releasing Peptide Has High Affinity and Efficacy at Neuropeptide FF2 Receptors

Abstract: Neuropeptide FF (NPFF) and prolactin-releasing peptide (PrRP) are two members of the RFamide peptide family. In this study we investigated whether these RFamide peptides, which have common structural features in their C-terminal RFamide motif and share several physiologically important functions, could exert their effects through the same set of receptors. The affinity and functional activity of several related RFamide peptides were determined at the human neuropeptide FF receptor subtype 2 (hNPFF2) and the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 31 publications
1
92
1
Order By: Relevance
“…Similarly, both the PrRP and the metastin receptors only bind their endogenous ligands (PrRPs and kisspeptins respectively) and are unaffected by other RFamides (Muir et al, 2001;Engstrom et al, 2003). In contrast, NPFF-1 and NPFF-2 receptors are relatively promiscuous and are activated by FMRFamide (Engstrom et al, 2003). However, both NPFF-1 and NPFF-2 can be blocked by the NPY-1 receptor antagonist BIBP3226 (Mollereau et al, 2001;Mollereau et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, both the PrRP and the metastin receptors only bind their endogenous ligands (PrRPs and kisspeptins respectively) and are unaffected by other RFamides (Muir et al, 2001;Engstrom et al, 2003). In contrast, NPFF-1 and NPFF-2 receptors are relatively promiscuous and are activated by FMRFamide (Engstrom et al, 2003). However, both NPFF-1 and NPFF-2 can be blocked by the NPY-1 receptor antagonist BIBP3226 (Mollereau et al, 2001;Mollereau et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…Thus other RFamides do not activate the QRFP receptors. Similarly, both the PrRP and the metastin receptors only bind their endogenous ligands (PrRPs and kisspeptins respectively) and are unaffected by other RFamides (Muir et al, 2001;Engstrom et al, 2003). In contrast, NPFF-1 and NPFF-2 receptors are relatively promiscuous and are activated by FMRFamide (Engstrom et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…RFRP-1 and -3 share a similar C-terminal sequence with NPFF (Table 1) and as discussed above RFRP analogues bind with relatively high affinity to the NPFF1 and NPFF2 receptors , Liu et al 2001, Engstrom et al 2003, first identified as cognate receptors for NPFF (Bonini et al 2000). NPFF1 exhibits a higher affinity for RFRP-1 and -3 than for NPFF and is now considered to be the endogenous RFRP receptor , Engstrom et al 2003.…”
Section: Lpxrfamide Familymentioning
confidence: 99%
“…Therefore, NPFF2 is now generally considered the endogenous receptor for NPFF, with NPFF1 as the RFRP receptor. However, NPFF2 appears to be fairly promiscuous, showing relatively high affinities for NPFF, RFRPs as well as prolactin-releasing peptide (PrRP; Engstrom et al 2003). Human NPFF1 and NPFF2 share 46% sequence identity and exhibit 31-37% identities with the receptors for orexin, neuropeptide Y, CCK 1 and PrRP.…”
Section: Npff Familymentioning
confidence: 99%
“…PrRP was also found to have high affinity to the NPFF2 receptor, resulting in anorexigenic effect (Engström et al 2003). The endogenous ligand of NPFF2 receptor, neuropeptide FF, also has hyperalgesic and antimorphine analgesic properties (for reviews, see Dockray 2004, Chartrel et al 2006.…”
Section: Prolactin-releasing Peptide In Food Intake Regulationmentioning
confidence: 99%